Groundwater denitrification using a continuous flow mode hybrid system combining a hydrogenotrophic biofilter and an electrooxidation cell. (1st August 2023) - Benekos, Andreas K.; Vasiliadou, Ioanna A.; Tekerlekopoulou, Athanasia G.; Alexandropoulou, Maria; Pavlou, Stavros; Katsaounis, Alexandros; Vayenas, Dimitris V.
Abstract: An attached-growth continuous flow hydrogenotrophic denitrification system was investigated for groundwater treatment. Two bench-scale packed-bed reactors were used in series, without external pH adjustment or carbon source addition, while inorganic carbonate salts already contained in the groundwater were the sole carbon source used by the denitrifying bacteria. The hydrogen was produced by water electrolysis using renewable energy sources thus minimizing resource-draining factors of the treatment process. The biofilter was subjected to a combination of three groundwater retention times (13.5, 27 and 54 min, corresponding to 20, 10 and 5 mL min −1 inlet water flow rates) and two hydrogen flow values (10 and 20 mL min −1 ) to evaluate its efficiency under different operating parameters. In all cases, significant nitrate percentage removals were achieved, ranged between 64.1% and 100%. The treatment process appears to slow down with lower retention times and H2 flow rate values, although residual nitrate concentrations were always in the range of 0–5.1 mg L −1, values below the maximum permitted limit of 11.3 mg L −1 . In cases where nitrite accumulation was detected, a continuous flow electrochemical oxidation process with three different current density values (5.0, 7.5 and 10.0 mA cm −2 ) was examined as a post-treatment step aiming to completely remove the toxic nitrite anions. Finally, an advanced mathematical model of the attached growth hydrogenotrophic denitrification process was developed to predict concentrations of all the substrates examined in the bio-filter (nitrate, nitrite, inorganic carbon and hydrogen). Graphical abstract: Image 1 Highlights: Hydrogenotrophic Denitrification (HD) of water was combined with Electrooxidation. The attached-growth HD biofilters achieved nitrate removal percentages of 64–100%. Electrooxidation led to nitrite removal percentages of up to 100%. A biofilm mathematical model of the HD process was applied and validated. Model predictions of HD process were accurate.